STRATEGI KOMUNIKASI PEMASARAN JASA FOTOGRAFI - Yanuar Ilham; Nugraha Sugiarta; Oky Mauludya Sudradjat (Universitas Informatika dan Bisnis Indonesia, 2021)
This research is titled Marketing Communication Strategy Photography services (case study of Personal Selling communication Model in maintaining the Wedding photography product line in Pixto Creative Studio in Bandung). This research explains the personal selling communication strategy and the competing strategy of photography services at Pixto Creative as part of the Integrated marketing communication mix and the service marketing mix that will be used as a reference for Pixto Creative to enhance communication tools to promote potential customers. The purpose of this research is to know the steps of personal selling communication, to know the advantages and disadvantages of personal selling communication, to know the steps to develop a competitive strategy of services, to know the marketing mix of services, and to know the main factors in maintaining the wedding photography product line of Pixto Creative. The research uses qualitative research methods with a case study approach, paradigm Research is constructivism where the personal selling communication done by Pixto Creative is the result of construction built by Pixto Creative so consumers will naturally receive such communications as part of reality. The data collection techniques in this study are documentation, interviews, and observations. The results of this research are the personal selling Pixto Creative steps include finding potential customers (prospecting) and qualifying, Pre-approach, presentations and demonstrations,